Optimal Packet Length for Free-Space Optical Communications with Average SNR Feedback Channel - Ghassan Alnwaimi; Hatem Boujemaa; Kamran Arshad (Journal of Computer Networks and Communications)
In this article, a method to enhance data rates of free-space optical (FSO) systems using packet length optimization is proposed. The average signal-to-noise ratio (ASNR) is measured at the receiver and sent back to the transmitter to optimize packet length. In addition, the length of packet is optimized to enhance the average throughput. We concluded that packet length can be reduced at low ASNR. However, packet length should be increased at higher values of received ASNR. For each ASNR, we also choose the optimal modulation and coding scheme (MCS) and optimal packet length to maximize the throughput. Different MCSs are investigated such as 4-pulse amplitude modulation (PAM) with and without channel coding, 8-PAM, 16-PAM, and 32-PAM. The proposed method gives 0.8–1.9 dB gain with respect to conventional FSO with adaptive modulation and coding (AMC) and fixed packet length. This is the first paper to deal with packet length optimization for FSO systems.